Rising Above Misinformation or Fake News in Africa: Another Strategy to Control COVID-19 Spread - Ahinkorah, Bright Opoku; Ameyaw, Edward Kwabena; Hagan, John Elvis; Seidu, Abdul-Aziz; Schack, Thomas (Frontiers in Communication, 2020)
Misinformation related to the COVID-19 pandemic is gradually gaining much popularity and amplifying the threat facing humanity about the continuous spread of the virus regardless of one’s location. Although some of the influx of these falsehoods may be harmless, others might pose a serious threat by misleading the general population to depend on unjustified and/ unsubstantiated claims for protection and show preference for them against scientifically proven guidelines. This paper provides a clear understanding on some COVID-19 misinformation, the inherent implications this poses to public health in Africa and highlights the potential strategies to curb this trend.